3D Hippocampal Place Field Dynamics in Free-Flying Echolocating Bats - Wohlgemuth, Melville J.; Yu, Chao; Moss, Cynthia F. (Frontiers in Cellular Neuroscience, 2018)
A large body of laboratory research has investigated the process by which environmental cues are acquired and used for spatial navigation in rodents; however, the key to differentiating between species specializations and general principles lies in comparative research. Rodent research has focused on a class of neurons in the hippocampus implicated in the representation of allocentric space – termed place cells – and the process by which these representations form. One class of models of hippocampal place field formation depends on continuous theta, a low frequency brain oscillation that is prevalent in crawling rodents. Comparative studies of hippocampal activity in echolocating bats have reported many findings that parallel the rodent literature, but also describe noteworthy species differences, especially with respect to theta rhythm. Here, we first discuss studies of the bat hippocampal formation and point to gaps in our knowledge, which motivate our new lines of inquiry. We present data from the free-flying laryngeal echolocating big brown bat, which shows 3-D place cells without continuous theta, similar to reports from the lingual echolocating Egyptian fruit bat. We also report findings, which demonstrate that the animal’s control over echolocation call rate (sensory sampling) influences place field tuning. These results motivate future comparative research on hippocampal function in the context of natural sensory-guided behaviors.